National HIV/AIDS policy : Jamaica (Ministry of Health [Kingston]JM, 2005)
Highlights the vision statement and outlines the objectives and guiding principles of the policy. Looks at the way forward and the implementation of the policy. Deals with its monitoring, evaluation and review.
Keywords: HIV